The China Agenda of International Studies. Who Are They and What Are They Talking About? [la Agenda China de Los Estudios Internacionales: ¿Quiénes Son y de Qué Hablan?] - Ross-Orellana, C; Toro-Ibacache, L (Universidad Complutense de Madrid, 2019)
The article explores the effects of the rise of China and the decline of the United States, in internationalist thinking and in the foreign policy of this country. The hypothesis that guides this article argues that the internationalists focused on the tensions generated by their foreign policy in the world, because the country was in a process of global repositioning that required strategies of recognition, expansion and consolidation, which aroused the suspicion of the world. For these reasons they should soften their discourse, diplomacy and actions, to advance without confronting, although assuming that China is increasingly a hegemonic power. To address this task, we used the reconstruction methodology of the study s agenda, in a corpus of authors and works abundantly cited by the specialists. The result of this analysis is structured in four parts, a conclusion and an annex where the detail of the corpus has been included. © UNISCI, 2019.